ASSESSMENT OF OLFACTORY FUNCTION BEFORE AND AFTER FUNCTIONAL ENDOSCOPIC SINUS SURGERY IN CHRONIC RHINOSINUSITIS - Raza, Tayyab Hassan; Hakim, Abdul; Ali, Muhammad; Raza, Maqbool; Junaid, Muhammad; Niazi, Saleem Asif (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the olfactory function in patients with chronic rhinosinusitis before and after functional endoscopic sinus surgery.Study Design: Descriptive cross-sectional study.Place and Duration of Study: Department of ENT, Combined Military Hospital, Rawalpindi, from Aug 2020 to Jul 2021.Methodology: We studied a total of 59 patients suffering from chronic rhinosinusitis. Patients with previous sinus surgery and immunosuppressed states were excluded. All participants underwent evaluation with a 5-point Likert scale and the Connecti- cut odor identification test both pre- and post-Functional endoscopic sinus surgery at 3 months post-procedure. Data were analyzed in SPSS version 26.Results: Our sample had a male to female ratio of 1.19:1. The mean age was 45.37 ± 14.25 years. A total of 37 (62.7%) patients reported an improvement of 19.2% in olfactory function post-FESS while 22 (37.2%) reported no difference or worsening ofolfaction.Conclusion: Functional endoscopic sinus surgery performed for chronic rhinosinusitis is associated with an improvement in olfactory function.